PENERAPAN STRATEGI PEMASARAN DAN REBRANDING PADA UMKM DESA TOAPAYA UTARA - Eka Kurnia Saputra; M Syafnur; Herman, Herman; Eko Murti Saputra; Indra Bastian Tahir; Muhammad Mu’azamsyah (Bajang Institute, 2025)
This research discusses the implementation of marketing and rebranding strategies in Micro, Small and Medium Enterprises (MSMEs) in North Toapaya Village. Against the background of the village's economic potential, this research aims to improve the competitiveness of MSMEs through training and mentoring in marketing management and product branding. The methods used include observation, interviews, and training that focuses on developing packaging designs, logos, and product legality such as PIRT Certificates. The results of this program show an increase in turnover, expansion of market reach, and increased consumer confidence in local products. It is hoped that the implementation of this strategy can be the first step to better economic growth for MSMEs in North Toapaya Village.